Usability evaluation model based on pedagogy, playability and mobility for mobile educational game - Al Fatta, Hanif (2023)
The research to propose a usability evaluation model for mobile educational games increased rapidly in recent years. The usability evaluation model was an effective tool for conducting usability evaluation during the software evaluation process. The high-quality model used in evaluating the usability aspect will ensure that the educational games show good quality and support their primary function in delivering educational content. This research proposed a comprehensive model to evaluate the usability of mobile educational games. This research suggested the PLATMO model, where three dimensions were proposed to measure playability, mobility and pedagogy. This study also presented suitable heuristics for each dimension to detect more usability issues during the usability testing. This research used a multi-methods methodology. The quantitative approach was employed to test the data by perfonning two round validation process. each round of validation involved more than 350 participants in collecting the data, followed by Confomatory Factor Analysis to evaluate the model fitness, ensuring the validity of the PLATMO Model. In addition, the qualitative approach was also employed by involving two participants serving as experts conducting the usability testing using a usability-meter prototype based on the proposed model. The result showed that PLATMO Model could be used as a fast and comprehensive tool for evaluation. Based on these results, this study succeeded in presenting two research contributions: the new model to measure usability and the usability prototype as a tool to conduct usability. New dimensions, such as learning assessment, could be added for foture development to enhance the PLATMO Model capabilit)'. PLATMO Model could also be used as a development guideline to produce good quality mobile educational games.